STUDI PENGENDALIAN KUALITAS PINTU KAYU DENGAN MENGGUNAKAN METODE LEAN SIX SIGMA - Sinaga, Tuti Sarma (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
This study is about the industry that produces wooden doors for export needs. The problems is the occurrence of defects in the production process and non value-added process. Type of defect commonly found on the wooden door is the assembly, gluing and coloring. This study aims to improve the quality of doors produced by reducing the number of defect products and reduce waste in the production floor. Lean Six Sigma is used to focus on reducing lead time and failure in the production process. Result shows that the main cause of defect products is low skill operators and machine during operation so that the product does not comply with the specified quality, The proposed improvement is to provide job training for operators, machine maintenance plan and make the procedure of operation activity on the Laminating, Glazing and assembly.